Critical Factors to Achieve Sustainability of Public-Private Partnership Projects in the Water Sector: A Stakeholder-Oriented Network Perspective - Nan He; Yijing Li; Huimin Li; Ziqi Liu; Chengyi Zhang (Complexity)
A key challenge in the management of the public-private partnership project is to understand the critical factors for sustainability performance as well as their complex interaction. Majority of existing studies focus on identifying general factors without consideration of specific context of individual sector. To bridge the gap, unique characteristics of water PPP projects are taken into consideration in this study where the relationship among critical factors to achieve sustainable performance is analyzed from a network perspective. Stakeholder-associated factors and their interrelations were identified via extensive literature review and structured interview, and the social network analysis (SNA) method was employed to recognize the critical factors and their interactions in sustainability achievement of water PPP projects. As a result, seven stakeholder groups and 18 critical factor nodes were identified and further classified into four challenges when achieving sustainability. These challenges are (1) promoting ecological awareness and responsible citizen behaviour; (2) project construction quality; (3) ecological designs and technology innovations; and (4) project management capacity. These findings provide the stakeholders of water PPP projects with useful references for mitigating the risks and facilitating efforts to achieve better sustainability performance.